Berichte über die IGU-Kommission Geomorphological Survey and Mapping nach der 12. Tagung in Lammi/Finnland 1977 - Leser, Hartmut (ERDKUNDE, 1978)
The IGU-commission on geomorphological survey and mapping is working about two projects: (1) the International Geomorphological Map of Europe 1:2,500,000, and (2) the book Geomorphology of Europe. Both are based on morphostructural approach. This approach, however, involves the danger that relief-forms and geomorphological processes stay in the background of morphostructural units. These units are permitted in the map, as both the morphogenetic context and the geomorphological synopsis are represented graphically, whereas the book Geomorphology of Europe has to start from coherent geomorphological units. This approach is in no way a geomorphologic-ecological one, but a geomorphogenetic one of the classic geomorphology. Discussions on recent morphodynamic research reveal that geomorphological processes of past ages were very complex, too. From this point of view the geomorphologists must estimate critically geo morphological approaches, theories, and models. The work of the IGU-commission on geomorphological survey and mapping should these discussions take into consideration.